Explanation:
The slope of the equation tangent to y = f(x) at x = 4 is equal to f'(4). Therefore,
![m = f'(4) = (1)/((4)^2 - 9) = (1)/(7)](https://img.qammunity.org/2022/formulas/mathematics/college/ig79uk4vfqkhu2h8qtmi9wmvlu2n0dwtiq.png)
We also know that the line passes through the tangent point at (4, -1) so we can write the slope-intercept form of the equation as
or
![b = -(11)/(7)](https://img.qammunity.org/2022/formulas/mathematics/college/3bicpejhq6ye0k0nn4jq2ikceisegdrq7q.png)
so our equation is
![y = (1)/(7)x -(11)/(7)](https://img.qammunity.org/2022/formulas/mathematics/college/an3otltc08z5f4xybrq7xm569ysia0avvj.png)
or in standard form,
![x - 7y = 11](https://img.qammunity.org/2022/formulas/mathematics/college/j6d0rxxz2l433515zmkiw0okmzhd33gxyt.png)